Modeling Of School Principal Supervision And Strengthening Teamwork And Teacher Job Satisfaction To Increase Organizational Commitment In The Era Of Educational 4.0 - Harijanto, Sutji; Sumardi, Sumardi; Hasanah, Yanah Uswatul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to test and analyze the direct and indirect influence of principal supervision, teamwork, and job satisfaction on organizational commitment in the era of educational 4.0. The unit of analysis is ASN (State Civil Apparatus) teachers at State Elementary Schools in Cicurug District, Sukabumi Regency. This research was conducted using survey methods, path analysis, and SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) analysis with a quantitative approach. The population in this study was 172 teachers and a sample of 121 teachers. Data analysis techniques were carried out using descriptive statistical analysis, analysis prerequisite tests, and SITOREM analysis. The research results show that (1) principal supervision has a positive influence on organizational commitment, (2) teamwork has a positive influence on organizational commitment, (3) job satisfaction has a positive influence on organizational commitment, (4) principal supervision has a positive influence on job satisfaction, (5) teamwork has a positive effect on job satisfaction, (6) principal supervision has a positive indirect effect on organizational commitment through job satisfaction, and (7) teamwork has a positive indirect effect on organizational commitment through job satisfaction. (8) it discovered the modeling of school principal supervision and strengthening teamwork and teacher job satisfaction to increase organizational commitment in the era of educational 4.0.